Food poisonings in Brazil – the impacts of the pandemic and its prevention perspectives (Research, Society and Development, 2021)
This study aimed to describe the epidemiological profile of food poisoning in Brazil with its trends and prospects for prevention, between the years 2016 and 2020. A cross-sectional, retrospective study with a quantitative approach was developed, the data for the research were taken from official government websites, namely: SINITOX (National System of Toxic-Pharmacological Information), DATASUS and IBGE (Brazilian Institute of Geography and Statistics). It became evident that a significant and sharp decrease in cases of food poisoning in Brazil and in its five socio-political regions (p